Fixed-Time Employment Agreement Based on Legal Awareness to Realize Harmonious Employment Relationship - Fithriatus Shalihah; Megawati Megawati; Suryadi Suryadi; Siti Zuliyah; Fauzan Muhammadi (Susbtantive Justice International Journal of Law, 2022)
The arrangement of fixed-time employment agreements stipulated in the laws and regulations of the Republic of Indonesia is considered ineffective. One of the primary reasons is that some existing provisions are deemed inappropriate for labor-market needs. Several articles concerning work agreements have been removed from the Job Creation Law, but implementation issues remain. Both are concerned with the fulfillment of workers' rights and the types of work that are permissible for workers with specific worker statuses at specific times. This research uses a normative juridical method with a statutory and conceptual approach. The result of analysis indicates that any employment agreement must include legal awareness provisions. This is done to provide a more concrete measure of legal awareness, because everything in the employment agreement is the result of an agreement reached by both parties. If there are impediments to the exercise of rights that are not the result of deliberate reason, the settlement has also been arranged using local wisdom in the form of deliberation between the parties. If the provisions of the laws and regulations regarding the fulfillment of the parties' rights cannot be run optimally, this can be a solution to create harmonious industrial relations. The most important solution to establishing the rule of law in creating a harmonious working relationship is legal awareness in the implementation of fixed-time employment agreements.